HNF1A-AS1: A Tumor-associated Long Non-coding RNA - Liu, Yuling; Zhao, Fangnan; Tan, Fangshun; Tang, Lu; Du, Zhuoying; Mou, Jie; Zhou, Gang; Yuan, Chengfu (Current Pharmaceutical Design, 2022)
Background: Hepatocyte nuclear factor 1 homeobox A antisense RNA 1 (HNF1A-AS1) is a Long non-coding RNA (LncRNA) that participates in the occurrence and development of lots of tumors and is supposed to be a new biomarker. The text aims to illustrate the biological effect, specific mechanism and clinical significance of HNF1A-AS1 in various tumors. Methods: Via consulting the literature, analyze and summarize the relationship between HNF1A-AS1 and all kinds of tumors and the specific mechanism. Results: This is a review paper about the tumor-associated long non-coding RNA HNF1A-AS1. Many researches show that LncRNA HNF1A-AS1 is related to the development of tumorous tumors. Its expression is up-regulated in numerous tumors, such as oral squamous cell carcinoma, hepatocellular carcinoma, breast cancer, osteosarcoma, lung cancer, cervical cancer, bladder cancer, colon cancer, colorectal cancer, oesophageal adenocarcinoma and laryngeal squamous cell carcinoma. However, HNF1A-AS1 is down-regulated in gastroenteropancreatic, neuroendocrine neoplasms, oral squamous cell carcinoma. Furthermore, HNF1A-AS1 can affect tumor proliferation, invasion, migration and apoptosis by targeting some microRNAs-miR-661 and miR-124. HNF1A-AS1 can also influence the development of tumors by regulating EMT. Conclusion: These studies show that LncRNA-HNF1A-AS1 is closely related to the occurrence development of numerous cancers. Through various molecular mechanisms to regulate tumor growth, HNF1A-AS1 can possibly become the new biological biomarker and therapeutic target for many kinds of tumors.
Keywords: Molecular mechanism